Phonon characteristics of Si‐doped InAs grown by gas‐source molecular beam epitaxy. (31st July 2019) - Talwar, Devki N.; Lin, Hao‐Hsiung; Feng, Zhe Chuan
Abstract: Using Raman scattering spectroscopy with 514‐ and 633‐nm light sources, we have studied the phonon characteristics of Si‐doped InAs films grown on (100) n‐type InAs by gas‐source molecular beam epitaxy having charge carrier concentration ( n ) between 2.26 × 10 18 and 1.68 × 10 20 cm −3 . The unscreened longitudinal optical (LO) phonon is observed near 238 cm −1 along with two plasmon‐LO‐phonon (PLP) coupled L± modes. With increasing n, the L− mode is downshifted from the LO phonon towards the transverse optical mode frequency. This abnormal behavior is ascribed to the large scattering vector and heavy Landau damping. The L+ mode close to the plasma frequency ω P is also detected in samples with n > 10 19 cm −3 . The observed unscreened LO mode in the forbidden configuration is attributed to the resonance enhanced scattering induced by surface space charge. Reliable values of charge carrier density and mobility are estimated from the simulated shifts of PLP modes in the low Si‐doped InAs films. At higher doping level, a full‐line shape analysis is desired for assessing accurate values of the transport parameters. In Si‐doped InAs, we appraised the existing experimental data of localized vibrational modes (LVMs) from Raman and Fourier transform infrared spectroscopy by exploiting a sophisticated Green's function theory and incorporating lattice relaxation effects around SiIn and SiAs defects for constructing accurate perturbation models. The simulated results of LVMs for several isolated ( T d ) defects, nearest neighbor pair ( C 3v ), and next‐nearest neighbor complex centers ( C s ) are compared, contrasted, and discussed with the experimental data. Abstract : Analysis of the Raman scattering measurements on Si‐doped MBE grown InAs samples with electron charge density ( n ) up to 1.68 × 10 20 cm −3 has offered unscreened LO phonon and two plasmon‐LO‐phonon coupled L± modes. As n is increased, the L− mode found downshifting from LO phonon towards the TO mode. This abnormal behavior is ascribed to large scattering vector and heavy Landau damping. In samples with n > 10 19 cm −3, the L+ mode close to plasma energy ω P is also detected. Second‐order Raman data are interpreted by accurate phonon dispersions ω ( q ) from a realistic lattice dynamical model using appropriate selection rules.